How much artificial surface storage is acceptable in a river basin and where should it be located: a review - Eriyagama, Nishadi; Smakhtin, Vladimir U.; Udamulla, Lakshika (Elsevier, 2020)
A key question in sustainable development is how much alteration in natural systems, such as river basins, is acceptable? One of the ways by which humans alter a river basin is by building water storage infrastructure. While storage reservoirs deliver numerous benefits, they can also induce social and environmental costs by displacing people, fragmenting river networks and altering downstream flow regimes. In such a context, merely capping total water withdrawal from rivers for human consumption is not sufficient. River basin plans should also identify optimal (acceptable) limits to surface storage capacities, and optimal numbers, degrees of distribution and locations of storage infrastructure. It remains largely unclear, however, whether it is possible to define a hydrologically, ecologically and socially justified ‘surface water storage boundary’ for a river basin. An associated question is what would be the ‘best’ arrangement of this bounding storage capacity in the basins river network (in terms of numbers, sizes and locations of reservoirs) to maximize water storage benefits and minimize environmental and social costs. The main objective of this review is to examine contemporary knowledge on surface water storage development with a focus on tools and approaches that may help to answer the above questions of a ‘surface water storage boundary’ and its ‘optimum arrangement’ for a river basin. In order to achieve this objective, our review introduces two novel concepts: the ‘storage scale’ and the ‘sustainable storage development framework.’ The ‘storage scale’ has four elements – capacity, number, distribution and location – individual scales that help visualize a ‘surface water storage boundary’ and its ‘optimum arrangement’ for a typical river basin. The ‘sustainable storage development framework’ consists of three dimensions – economic benefits, ecosystems and society- and a set of indicators quantifying each dimension. This review shows that optimal levels of the elements of the ‘storage scale’ may be identified using the ‘sustainable storage development framework’.